Nikander's Thesis: Studies on the exocrine ducts of the pancreas and the liver in reindeer (Rangifer tarandus tarandus L) - Sven Nikander (Rangifer, 1991)
This thesis is based on the following papers, which will be referred to in the next by their Roman numerals: I Nikander, S. 1990. On the anatomy and topography of the pancreas and the pancreatic duct in reindeer (Rangifer tarandus tarandus L.). Rangifer 10: 25-29. II Rahko, T. & Nikander, S. 1990. Macroscopical and microscopical studies of the common bile duct in reindeer (Rangifer tarandus tarandus L.). Rangifer 10: 3-8. III Rahko, T. & Nikander, S. 1990. Histochemical studies of the common bile duct in reindeer. Rangifer 10: 9-15. IV Rahko, T. & Nikander, S. 1990. Electron microscopical studies of the common bile duct in reindeer. Rangifer 10: 17-23. V Nikander, S. & Rahko, T. 1990. Ultra-structure of granulated cells in the bile duct of reindeer. Rangifer Special Issue No. 3: 363-367.